Effects of partially replacing fishmeal with corn gluten meal on growth, feed utilization, digestive enzyme activity, and apparent nutrient digestibility for juvenile white shrimp, Litopenaeus vannamei - Lin, Huaxing; Deng, Yingkai; Zhu, Dongwenjun; Yang, Qihui; Zhou, Xiaoqiu; Tan, Beiping; Feng, Lin; Chi, Shuyan (Frontiers in Veterinary Science, 2023)
This experiment was conducted to assess the possibility of replacing fishmeal (FM, the base group fishmeal 30%) with corn gluten meal at different levels—0% (Crude protein: 401.50 g·kg-1; Crude lipid: 87.60 g·kg-1; Gross energy: 19.28 MJ·kg-1), 10% (Crude protein: 403.60 g·kg-1; Crude lipid: 86.50 g·kg-1; Gross energy: 19.41 MJ·kg-1), 20% (Crude protein: 404.90 g·kg-1; Crude lipid: 86.60 g·kg-1; Gross energy: 19.69 MJ·kg-1), 30% (Crude protein: 402.20 g·kg-1; Crude lipid: 85.20 g·kg-1; Gross energy: 19.64 MJ·kg-1), 40% (Crude protein: 406.40 g·kg-1; Crude lipid: 85.40 g·kg-1; Gross energy: 19.51 MJ·kg-1), and 60% (Crude protein: 405.90 g·kg-1; Crude lipid: 86.50 g·kg-1; Gross energy: 19.56 MJ·kg-1), respectively—and its effects on growth, feed utilization, digestive enzyme activity and apparent nutrient digestibility for juvenile white shrimp, Litopenaeus vannamei. Seven hundred twenty healthy and uniformed-size shrimp were distributed to six groups of three replicates, each with 40 shrimp in each tank. Each experimental diet was fed to shrimp four times daily to apparent satiation, for 8 weeks. At the end of the experiment, the total weight of fish in each tank was weighed and randomly selected for testing, including fish nutrient composition and digestive enzyme activity. Results showed that no significant differences were observed in the weight gain rate, feed coefficient rate and specific growth rate of shrimp after 30% FM was replaced with CGM, but these indicators were on a downward trend. As CGM content increased, the content of crude protein and phosphorus in the shrimp decreased significantly, whereas the crude fat content first increased significantly and then decreased. Amylase activity was significantly reduced with CGM increased. As CGM content increased, the digestion of energy and dry matter was first significantly increased and then significantly decreased. The digestibility of all amino acids (AA), except methionine (Met) and arginine (Arg), was significantly lower in the control group after CGM replacement of 30% FM. In summary, FM could be partially replaced by CGM in the feed of L. vannamei. Based on the broken-line regression analysis of WGR, the optimal dietary CGM replacement was 27.47%.